Analisis Ketimpangan Ekonomi Provinsi Bali Tahun 2019 - Ukhti Luthfiyah; Amandus Jong Tallo (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2020)
Bali Province has different quantity and quality of natural resources in each area. These differences lead to inequality or disparity between its districts and city. The purpose of this study is determine the economic inequality according to the region and business sectors in the Province of Bali. The data in this study use the secondary data of Gross Regional Domestic Product (GRDP) on Constant Prices from 2015 to 2019 taken from Central Bureau of Statistics (BPS) every area in the Province of Bali. This research was determined by the Klassen typology analysis method and the determination of regional disparities using the Williamson Index. The results of this study indicate that the Province of Bali has an inequality value of the Williamson Index of 0.26 in 2019 which shows a pretty good value with a decrease in the level of economic inequality compared to research in the previous year. Equitable development must still be considered by focusing on regions and sectors that are still lagging behind or underdeveloped, so that the development process can occur in all region of Bali Province.